Open and Distance Learning: A Veritable Tool for Enhancing Gender Equality in Higher Education - Nnaka, Chibuogwu V. (West African Journal of Open and Flexible Learning, 2014)
Several studies and available evidence reveal that women in Nigeria have been denied access to education due to socio-cultural practices and religious beliefs. Women are therefore grossly disadvantaged in education especially in higher education. The advent of the National Open University of Nigeria (NOUN) has provided wider access to higher education for all including women through the open and distance learning (ODL) mode. Many women who could not attend conventional universities are now enrolled in NOUN higher education programmes. This study sought to determine the socioeconomic and personal factors that influenced the enrolment of women into NOUN higher education programmes. It also sought to find out if there are any constraints facing the women enrolled in NOUN higher education programmes. Three research questions were raised for the study. A 20-item questionnaire was developed for the study. The face and content validity of the questionnaire was determined by experts in ODL. A pilot test was used to establish the reliability of the questionnaire. A reliability coefficient of 0.81 was obtained. Five hundred women enrolled in NOUN higher education programmes were drawn from five randomly selected study centres in Nigeria using the random sampling technique. Data collected were analysed using descriptive statistics. The findings revealed that the flexibility of ODL and the need to acquire higher qualifications for promotion and elimination of gender inequalities were the major factors that influenced the women to enroll in NOUN higher education programmes. Inadequate computer skills were also identified as the greatest constraint faced by the women. Recommendations were made for equipping women with the necessary computer skills needed for ODL and also for enhancing women’s access to higher education programmes of NOUN.